Akibat Hukum Antara Produsen Kue Tradisional dengan Distributor dalam Perjanjian Konsinyasi (Titip Jual) di Denpasar Selatan - I Nyoman Vinata Aditya (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to find out the factors that cause breach of promise in carrying out the obligations listed in the consignment agreement between traditional cake producers and distributors in South Denpasar as well as to find out the legal consequences of consignment agreements between traditional cake producers and distributors in South Denpasar. This scientific work in giving discussion uses empirical research methods. The factors causing the default are late payment, an increase in cake raw materials, and negligence on the part of the consignee. As a result of the Consignment Agreement Law implemented by Traditional Cake Producers and Distributors in South Denpasar, there will be an imbalance between the rights and obligations that have been agreed orally by both parties. Even though in the cooperation between the producer and the distributor by making an oral consignment agreement, that the oral agreement is a valid agreement and does not contradict article 1230 of the Civil Code regarding the legal conditions of the agreement, when the oral consignment agreement is made without an agreement between the two parties, the parties are not of legal age, there is no object to be agreed upon and for some reason it is not the case, the agreement is contrary with Article 1230 of the Civil Code which can be revoked and null and void.